Criticism, Gender and Discourse in Chamber-music Concerts in Madrid at the Beginning of the Twentieth Century - Hernández Polo, Beatriz (Cuadernos de Música Iberoamericana, 2021)
The growing success of performances organised by entities such as the Sociedad Filarmónica or the Cuarteto Francés in Madrid during the first decade of the twentieth century was backed up by an increasing interest in chamber music from music critics in local newspapers. This article will provide various examples of texts from newspapers that covered their concerts. Its objective is to examine the connections and similarities that were established between the male and female condition and the processes of chamber music that, indirectly, reveal how the participation of women in all facets of music was viewed. In addition, it will also show how this criticism regularly incorporated resources and discursive constructions largely related with gender stereotypes that are linked to musical processes including composition, performance and reception.